Clinical and Epidemiological Characteristics of Ischemic Stroke Patients in Samarkand Region: A Retrospective Study - Nodir, Saidov; Ziyadulloyevna, Xakimova Soxiba (American Journal of Biomedicine and Pharmacy, 2025)
Ischemic stroke is a leading cause of disability and mortality worldwide, with increasing incidence in developing countries including Uzbekistan. This study aimed to analyze the clinical presentations, risk factors, diagnostic challenges, and outcomes of ischemic stroke patients admitted to the Samarkand regional hospital. By retrospectively reviewing medical records of 150 patients over two years, we identified key epidemiological trends and clinical profiles. Findings reveal hypertension and diabetes mellitus as predominant risk factors, with a significant portion of patients presenting with motor deficits and speech disturbances. Delays in hospital admission and limited access to advanced imaging were notable challenges impacting timely management. This study emphasizes the urgent need for enhanced stroke awareness, rapid diagnosis, and improved healthcare infrastructure in the Samarkand region. Ischemic stroke remains one of the leading causes of morbidity and mortality worldwide, particularly impacting developing countries such as Uzbekistan. Despite significant advances in stroke management globally, many regions including Samarkand still face challenges related to timely diagnosis, effective treatment, and adequate rehabilitation services. This retrospective study aims to comprehensively evaluate the clinical and epidemiological characteristics of ischemic stroke patients admitted to Samarkand Regional Hospital over a two-year period. Data from 150 patients were analyzed to identify demographic patterns, prevalent risk factors, presenting symptoms, diagnostic modalities, treatment approaches, and short-term outcomes. The findings reveal a predominance of traditional vascular risk factors such as hypertension and diabetes mellitus, with the majority of patients experiencing delayed hospital admission, thus limiting their access to acute interventions like thrombolysis. Motor deficits and speech impairments were the most common clinical presentations. The study underscores the urgent need for enhanced public awareness, improved emergency stroke services, and expansion of diagnostic and therapeutic resources to reduce the burden of stroke-related disability and mortality in the region. These insights provide a foundation for targeted healthcare policy and resource allocation to improve stroke care delivery in Samarkand and similar settings.